Haptic and Audio Interaction Design 4th International Conference, HAID 2009 Dresden, Germany, September 10-11, 2009 Proceedings - Altinsoy, M. Ercan; Jekosch, Ute; Brewster, Stephen (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the 4th International Workshop on Haptic and Audio Interaction Design, HAID 2009 held in Dresden, Germany in September 2009. The 17 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections on haptic communication and perception, navigation and guidance, visual impairment, vibrotactile feedback and music, multimodal user interfaces: design and evaluation, and multimodal gaming.